The Psychological and Spiritual Motivations Behind Digital Alms Giving - Rahayu, Ena Bhekti; Nuraeni, Meiyanda Eka; Hadzik, Imam Nur; Saputra, Anas Ragil (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The research aims to identify the internal emotional, cognitive, and faith-based factors that influence charitable behavior through digital platforms, and how these motivations reflect the interplay between modern technology and traditional religious values.The advent of digital technology has had a profound impact on the domain of digital charity. The present study aims to analyse the psychological and spiritual factors that influence digital charity by Indonesians. The collection of data was achieved through the administration of questionnaires to 73 respondents and in-depth interviews with five individuals, as part of a mixed-method approach and explanatory sequential design. This research can demonstrate that straightforward and transparent access can be the primary factor that propels digital charity. From a psychological perspective, the desire to participate and provide benefits to others can have a positive impact. Spiritually, sincerity in one's intentions, the expression of gratitude, and the establishment of a sense of trust in the process of giving alms via digital platforms have been shown to be conducive to the experience of blessings.